2022
DOI: 10.2147/oaem.s382752
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Performance of the NEWS‒Lactate and NEWS Towards Mortality or Need for Critical Care Among Patients with Suspicion of Sepsis in the Emergency Department: A Prospective Observational Study

Abstract: We aimed to evaluate the National Early Warning Score-Lactate (NEWS-L) and NEWS to predict 24-hour mortality as the primary outcome. The secondary outcomes were to predict 48-hour, 28-day, and in-hospital mortality rates, and the need for critical care in patient with suspicion of sepsis at the emergency department (ED). Methods: A prospective observational study was performed in patients aged ≥18 years diagnosed with sepsis in the ED from March to November 2021. Area under the receiver operating characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Anyway, we can confirm that, for the analysis of infected patients, the AUC for predicting 2-day mortality and consequently immediate probability risk of death, continues to be good, and exceeds that obtained by both qSOFA and NEWS2 in our study, as well as that obtained by other studies. Dadeh et al (22) analyzed the predictive capacity of 2-day mortality NEWS and NEWS-Lactate among infected patients and obtained AUCs of 0.79 and 0.81 respectively, again lower than those obtained by mSOFA. On the other hand, if we analyze the predictive capacity of qSOFA and prehospital NEWS for 30-day mortality, the AUCs decrease slightly, as demonstrated by Silock et al (23) who obtained AUCs of 0.68 for qSOFA and 0.73 for NEWS2, figures much lower than the performance of mSOFA.…”
Section: Discussionmentioning
confidence: 96%
“…Anyway, we can confirm that, for the analysis of infected patients, the AUC for predicting 2-day mortality and consequently immediate probability risk of death, continues to be good, and exceeds that obtained by both qSOFA and NEWS2 in our study, as well as that obtained by other studies. Dadeh et al (22) analyzed the predictive capacity of 2-day mortality NEWS and NEWS-Lactate among infected patients and obtained AUCs of 0.79 and 0.81 respectively, again lower than those obtained by mSOFA. On the other hand, if we analyze the predictive capacity of qSOFA and prehospital NEWS for 30-day mortality, the AUCs decrease slightly, as demonstrated by Silock et al (23) who obtained AUCs of 0.68 for qSOFA and 0.73 for NEWS2, figures much lower than the performance of mSOFA.…”
Section: Discussionmentioning
confidence: 96%
“…deterioration in patients with different clinical beyond cases of sepsis, in which its use is evident. [26][27][28][29][30] Hence, different studies reported its use in association with other scores: associated to ViEWS, it improves the prognosis of mortality in critical and major trauma patients 16,17 ; when associated to Modified Early Warning Score (MEWS) it improves accuracy with respect to admission to the ICU 29 ; when used with NEWS2, it detects the risk of 2-day in-hospital mortality in the ED setting. 22,31 Although its effectiveness is questionable when it is used indiscriminately among general patients in emergency services, contradictory results are reported between different authors.…”
Section: Discussionmentioning
confidence: 99%
“…The use of lactate in combination with different EWSs is not new. Since 2013 when Jo et al 21 combined it with ViEWS, numerous studies have tested it in different populations, demonstrating that the use of biomarkers, and specifically lactate, is very useful for identifying clinical deterioration in patients with different clinical conditions beyond cases of sepsis, in which its use is evident 26–30 . Hence, different studies reported its use in association with other scores: associated to ViEWS, it improves the prognosis of mortality in critical and major trauma patients 16,17 ; when associated to Modified Early Warning Score (MEWS) it improves accuracy with respect to admission to the ICU 29 ; when used with NEWS2, it detects the risk of 2‐day in‐hospital mortality in the ED setting 22,31 .…”
Section: Discussionmentioning
confidence: 99%